Variation and constraints of local adaptation of a long-lived plant, its pollinators and specialist herbivores - Kalske, A; Muola, A; Laukkanen, L; Mutikainen, P; Leimu, R (2012)
Due to geographically variable species interactions, plants may become locally adapted to their sympatric herbivores and pollinators. However, adaptation to the abiotic environment may significantly affect plant interactions with herbivores and pollinators. Local adaptation to the abiotic environment may constrain local adaptation to herbivores and pollinators under contrasting selection pressures, resulting in trade-offs in local adaptation. We studied local adaptation of a perennial herb, Vincetoxicum hirundinaria, in a reciprocal transplant experiment among four populations and measured plant fitness, pollination success and resistance to two specialist herbivores. We also estimated local adaptation of these two herbivores and generalist pollinators to their sympatric plant populations. Local adaptation was compared with within-population genetic variation, genetic and geographical divergence, and with divergence in terms of population size, environmental conditions and plant secondary chemistry. We further compared local adaptation to the environment, to local adaptation to herbivores and pollinators to detect possible trade-offs in local adaptation. The existence and degree of local adaptation varied among the plant populations. Plants from two populations were locally adapted to their sympatric leaf herbivores and plants from two populations were locally adapted to their abiotic environment. Herbivores from one population were locally adapted to their sympatric plant population. Local adaptation of V. hirundinaria to the seed predator increased with increasing among-population divergence in precipitation and temperature. Local adaptation to the seed predator and the environment increased with increasing population genetic variation. Local adaptation of V. hirundinaria in fitness and in herbivore resistance also correlated positively, suggesting lack of trade-offs in local adaptation. Synthesis. These results demonstrate that species interactions can lead to a mosaic of locally adapted plant, herbivore and pollinator populations. In addition to natural enemies, genetic variation, the abiotic environment and mutualistic interactions contribute to the evolution of local adaptation in long-lived plants. These results provide new insights into the patterns and causes of variation in local adaptation and are among the first to demonstrate that conflicting selection pressures within a population do not constrain local adaptation in multiple traits. © 2012 The Authors. Journal of Ecology © 2012 British Ecological Society.